The UNCITRAL model law and Asian arbitration laws : implementation and comparisons / edited by Gary F. Bell, National University of Singapore. - Bell, Gary F. (Cambridge University Press, 2018)
In the Asia-Pacific, thirty-eight jurisdictions have adopted the UNCITRAL Model Law on International Commercial Arbitration. This book looks at how the text and the principles of the Model Law have been implemented (or not) in key Asian jurisdictions. Most of the jurisdictions covered in this book have declared that they have adopted the Model Law but often with significant modifications. Even when jurisdictions adopt some provisions of the Model Law verbatim, their courts may have interpreted these provisions in a manner inconsistent with their goals and with how they are interpreted internationally. When a jurisdiction has not adopted the Model Law, the chapter compares its legislation to the Model Law to determine whether it is consistent with its principles. Each chapter follows the structure of the Model Law allowing the reader to easily compare the arbitration laws of different jurisdictions on each topic.